REFORMASI PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI: MENUJU PENDIDIKAN BERKUALITAS DAN BERDAYA SAING GLOBAL - Susiyati; Sihono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the challenges faced by State Islamic Religious Higher Education Institutions (PTKIN) in enhancing competitiveness and education quality in the era of globalization and proposes strategic steps for reform. The method employed is a library research approach with descriptive and analytical analysis. Data were collected from various recent and relevant literature sources and analyzed using thematic and critical literature methods. The results reveal that PTKIN faces major challenges in integrating religious and general sciences, infrastructure limitations, and readiness to adopt modern educational policies such as Merdeka Belajar Kampus Merdeka (MBKM). Additionally, PTKIN encounters institutional governance issues and foreign language proficiency constraints. The findings suggest the necessity of curriculum reform that integrates religious and general sciences, improving educators' competencies, and strengthening collaboration with external stakeholders. The study concludes that strategic reforms based on Islamic values and technological advancements are crucial for PTKIN to become a globally competitive higher education institution while remaining relevant to contemporary developments. Keywords: Higher Education Reform, Integrative Curriculum, Global Competitiveness.